The Influence of Mineral Fertilizer Combined With a Nitrification Inhibitor on Microbial Populations and Activities in Calcareous Uzbekistanian Soil Under Cotton Cultivation - Dilfuza Egamberdiyeva; Muhiddin Mamiev; Svetlana K. Poberejskaya (The Scientific World Journal)
Application of fertilizers combined with nitrification inhibitors affects soil microbial biomass and activity. The objective of this research was to determine the effects of fertilizer application combined with the nitrification inhibitor potassium oxalate (PO) on soil microbial population and activities in nitrogen-poor soil under cotton cultivation in Uzbekistan. Fertilizer treatments were N as urea, P as ammophos, and K as potassium chloride. The nitrification inhibitor PO was added to urea and ammophos at the rate of 2%. Three treatments—N200P140K60 (T1), N200 P140 POK60 (T2), and N200 P140 POK60 (T3) mg kg-1 soil—were applied for this study. The control (C) was without fertilizer and PO. The populations of oligotrophic bacteria, ammonifying bacteria, nitrifying bacteria, denitrifying bacteria, mineral assimilating bacteria, oligonitrophilic bacteria, and bacteria group Azotobacter were determined by the most probable number method. The treatments T2 and T3 increased the number of oligonitrophilic bacteria and utilization mineral forms of nitrogen on the background of reducing number of ammonifying bacteria. T2 and T3 also decreased the number of nitrifying bacteria, denitrifying bacteria, and net nitrification. In conclusion, our experiments showed that PO combined with mineral fertilizer is one of the most promising compounds for inhibiting nitrification rate, which was reflected in the increased availability and efficiency of fertilizer nitrogen to the cotton plants. PO combined with mineral fertilizer has no negative effects on nitrogen-fixing bacteria Azotobacter and oligo-nitrophilic bacteria.